Stuck in the middle with you: Conceptualizing data intermediaries and data intermediation services - Julia Schweihoff; Anzelika Lipovetskaja; Ilka Jussen-Lengersdorf; Frederik Möller (Electronic Markets, 2024)
Abstract Data intermediation services are a novel class of services mitigating various aspects of inter-organizational data sharing. Facilitating data intermediation services is a pivotal activity that leverages the benefits of the data economy. These services are usually provided by so-called data intermediaries, who organize data sharing between one or multiple data provider(s) and data consumer(s). Against the background of prominent legislation, these data intermediaries (e.g., data marketplaces or data trusts) receive increasing attention in research, practice, and politics. For instance, the Data Governance Act regulates data intermediation services, prompting organizations sharing data to comply with various regulations, including registration with government bodies or acquiring a trusted label. However, to date, little research has been done about the nature of data intermediation services, motivating us to tackle this issue in a two-fold strategy. First, we derive a visualization of a data intermediary and concept subsuming its potential functions. Second, we explore archetypical configurations of co-existing services of data intermediaries. With this, we contribute to understanding the data intermediaries as a concept and enrich this understanding with more detailed service configurations.
Additional information: A1
Keywords: 330; Data intermediaries; Archetypes; Data sharing; Taxonomy